Scratch2, a Snail Superfamily Member, Is Regulated by miR-125b - Goes, Carolina Purcell; Vieceli, Felipe Monteleone; De La Cruz, Shirley Mirna; Simões-Costa, Marcos; Yan, Chao Yun Irene (Frontiers in Cell and Developmental Biology, 2020)
Scratch2 is a transcription factor expressed in a very restricted population of vertebrate embryonic neural cell precursors involved in their survival, differentiation, and migration. The mechanisms that control its expression remain unknown and could contribute towards our understanding of gene regulation during neural differentiation and evolution. Here we investigate the role of microRNAs (miRNAs) in the Scrt2 post-transcriptional regulatory mechanism. We identified binding sites for miR-125b and -200b in the Scrt2 3’UTR in silico. We confirmed the repressive-mediated activity of the Scrt2 3’UTR through electroporation of luciferase constructs into chick embryos. CRISPR/Cas9-mediated deletion of miR-125b/-200b responsive elements from chicken Scrt2 3’UTR and expression of miRNAs sponges to deplete their activity in the neural tube. Both strategies increased Scrt2 expression field, suggesting a role as post-transcriptional regulators of Scrt2. However, the biological effect of miR-125b titration was much more pronounced than that of miR-200b. Therefore, we propose that, after transcription, miR-125b fine-tunes the Scrt2 expression domain.